Tren Dalam Ekonomi Politik Komunikasi - Hendrawati, Lely; Rusadi, Udi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The globalization of the field, the expansion of a long-standing emphasis on historical research, the growth of research from alternative viewpoints, particularly feminism and labor, the shift from an emphasis on old to new media, and the growth of activism linked to the political economy tradition are five major trends in the political economy of communication that are addressed in this paper. None of them are really new trends; rather, they build on earlier ones that were frequently buried behind more prevalent ones at the time. However, the results of particular battles within each of these areas point to political economists as having significantly contributed to the general upsurge in activity surrounding important communication concerns. Keywords: Globalization, feminism, labor, political economy of communication, communication history, and activism